WEB-BASED INFORMATION SYSTEM DESIGN OF SATE CILEBUT STORE - Nisaa, Istiqoomatun; Firdaus Malik, M. Nanda; S. N., Hartanto (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
Selling is a concerted effort to develop a strategic plan aimed at satisfying the needs and buyer desires to generate profitable sales. With the development of information and communication technology, the authors propose designing a web-based kedai sate information system, a system that can produce information accurately, efficiently, on time, and relevant and can be linked between admin, finance, and warehouse to improve in each area performance. The design of this information system is expected to be able to promote via the internet and administrators can process data on purchases and sales so that the data reporting system can be found easily, quickly, and accurately.